Cellular Pushing Forces during Mitosis Drive Mitotic Elongation in Collagen Gels - Sungmin Nam (Advanced Science, 2021)
Abstract Cell elongation along the division axis, or mitotic elongation, mediates proper segregation of chromosomes and other intracellular materials, and is required for completion of cell division. In three‐dimensionally confining extracellular matrices, such as dense collagen gels, dividing cells must generate space to allow mitotic elongation to occur. In principle, cells can generate space for mitotic elongation during cell spreading, prior to mitosis, or via extracellular force generation or matrix degradation during mitosis. However, the processes by which cells drive mitotic elongation in collagen‐rich extracellular matrices remains unclear. Here, it is shown that single cancer cells generate substantial pushing forces on the surrounding collagen extracellular matrix to drive cell division in confining collagen gels and allow mitotic elongation to proceed. Neither cell spreading, prior to mitosis, nor matrix degradation, during spreading or mitotic elongation, are found to be required for mitotic elongation. Mechanistically, laser ablation studies, pharmacological inhibition studies, and computational modeling establish that pushing forces generated during mitosis in collagen gels arise from a combination of interpolar spindle elongation and cytokinetic ring contraction. These results reveal a fundamental mechanism mediating cell division in confining extracellular matrices, providing insight into how tumor cells are able to proliferate in dense collagen‐rich tissues.